Development and characterization of myofibrillar protein film obtained from Nile tilapia mechanically separated meat (MSM) - Oliveira Leite, Lana; Monaliza Sousa Nogueira, Sara; Irene Martins da Silva, Ana; Alves do Vale, Diego; Araújo Cerqueira, Davi; Luis Coelho da Silva, André; Moreira de Souza Filho, Men de Sá; Warlene Silva de Souza, Bartolomeu (Revista Ciência Agronômica, 2024)
Processing residues are still one of the main obstacles in the fishing industry due to waste and environmental impact. With that, ways of reusing these residues are researched to generate new products with different applications. The objective of this work was to develop and evaluate protein films obtained from mechanically separated meat (MSM) of Nile tilapia (Oreochromis niloticus) filleting residues. To get the films, the casting technique was used, varying their composition in relation to the amount of protein (1.0, 1.5 and 2.0%) and glycerol (0.0, 0.1 and 0.2%), creating a 3² factorial plan, with 9 treatments. The films were characterized in terms of color, opacity, water solubility, mechanical properties and water vapor permeability (WVP). In the end, a yield of 18.70% of Nile tilapia myofibrillar proteins (MPs) and a post-lyophilization protein content of 87.33% were obtained. It was concluded that the film that presented the best result in all the characteristics analyzed was the one with 1.0% of MPs and 0.1% of glycerol.